(untitled) (Ozone Therapy Global Journal, 2012)
In condition of reproduction of hemorrhagic shock according to Wigger’s experimental model, the efficacy of systemic use of ozonotherapy together with infusion therapy of hypovolemic con ditio n. It has been sh own that the infus i on of ozonized saline strengt hens adaptable re actions of r esp iratory an d gas transpor t syst em s. Oz one increases the level of serotonin in the blood, decreases the frequency of respiration and increases volume of respiration and oxygen consumption.